Evaluación de encapsulados para el control de contaminantes emergentes en aguas (2021)
The purpose of this project is to evaluate the encapsulation for the control of emerging pollutants in waters. Initially, a contextualization of the water problem and identification of wastewater was carried out, as well as the definition of emerging pollutants, their classification, source, destination and effects on the environment, humans and economically. Following this, current treatment systems were identified and adsorption, its models and kinetics, as well as adsorbent solids are presented to give an understanding of encapsulation. From a search and selection of bibliographic reviews (Scopus, Science Direct, Knovel) from the year 2010-2021, it was possible to recognize the presence of emerging pollutants in water in a global context, by continents and finally in Colombia. The foregoing made it possible to segment the research into antibiotics, analgesics and anti-inflammatories as contaminants with a high presence in wastewater, measured mainly in WWTPs, coming from hospital-type wastewater and from pharmaceutical industries.